2011
DOI: 10.1128/jcm.02207-10
|View full text |Cite
|
Sign up to set email alerts
|

Increase in Prevalence of Streptococcus pneumoniae Serotype 6C at Eight Children's Hospitals in the United States from 1993 to 2009

Abstract: Streptococcus pneumoniae serotype 6C, which was described in 2007, causes invasive disease in adults and children. We investigated the prevalence of 6C among pediatric isolates obtained from eight children's hospitals in the United States. S. pneumoniae isolates were identified from a prospective multicenter study (1993 to 2009). Fifty-seven serotype 6C isolates were identified by multiplex PCR and/or Quellung reaction. Five were isolated before 2000, and the prevalence increased over time (P < 0.000001). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0
3

Year Published

2013
2013
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 25 publications
3
24
0
3
Order By: Relevance
“…The presence of 8 STs found among only 27 serotype 6C isolates in this study are consistent with other studies that have described a high degree of genetic diversity among this serotype (Campos et al, 2009;Carvalho et al, 2009;Green et al, 2011;Jacobs et al, 2009;Nunes et al, 2009;Rolo et al, 2011b). Of the 8 STs of serotype 6C isolates reported in this study, 4 (1390, 1379, 473, and 1292) have been previously associated with serotype 6A.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…The presence of 8 STs found among only 27 serotype 6C isolates in this study are consistent with other studies that have described a high degree of genetic diversity among this serotype (Campos et al, 2009;Carvalho et al, 2009;Green et al, 2011;Jacobs et al, 2009;Nunes et al, 2009;Rolo et al, 2011b). Of the 8 STs of serotype 6C isolates reported in this study, 4 (1390, 1379, 473, and 1292) have been previously associated with serotype 6A.…”
Section: Discussionsupporting
confidence: 81%
“…While ST2899 and ST4285 found in this study are associated solely with serotype 6C, they are double-and triple-locus variants, respectively, of ST1390. Other studies have reported similar findings Green et al, 2011;Jacobs et al, 2009). Among the serotype 6C isolates analyzed by Jacobs et al (2009), 9 MLST clusters were identified.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations